Private University - Dave, N. R. (Journal of Engineering Education Transformations, 2006)
Higher Education in Thrmoil Formal higher and professional education is in great flux in this country. On one hand, establishing national statutory councils, to prescribe norms and standards in order to monitor enforcement of the same, happened through legislation; while on the other hand, private initiative to shoulder the burden of establishing and running the institutes was made possible by the directions of the Apex Court.